Technology and Corporate Scope: Firm and Rival Innovation as Antecedents of Corporate Transactions - Kaul, Aseem (Strategic Management Journal, 2012)
This paper studies the role of technological innovation as an antecedent of changes in corporate scope. It argues that technological innovations prompt the firm to reconfigure its corporate portfolio—to redeploy resources to areas of new opportunity while it divests out of marginal businesses. Results from a cross‐industry sample of U.S. manufacturing firms show successful innovation by a firm is followed by both expansion into new areas through complementary resource seeking acquisitions and divestment out of existing noncore businesses. This relationship is found to be moderated by the level of investible resources available to the firm, and supports the notion of scarce resources as a constraint on firm scope. In addition, firms are found to change their corporate scope in response to rival innovation. Copyright © 2011 John Wiley & Sons, Ltd.